Perineural Dexmedetomidine Reduces the Median Effective Concentration of Ropivacaine for Adductor Canal Block - Wang, Chunguang (Med Sci Monit, 2021)
BACKGROUND: Multimodal analgesic regimens are well known as the best option for total knee arthroplasty. They include the adductor canal block, combined with local infiltration analgesia and a block of the interspace between the popliteal artery and the capsule of the posterior knee. However, these analgesic techniques all require a large amount of local anesthetics. In this study, we explored whether the quantity of local anesthetics could be decreased by using dexmedetomidine for the adductor canal block. MATERIAL/METHODS: Fifty-four patients scheduled for unilateral, primary total knee arthroplasty were allocated into 2 groups: the ropivacaine group (group R) and the dexmedetomidine group (group RD). Ropivacaine 0.5% was chosen as the initial concentration, and the concentration was decreased or increased according to the response of the previous participant. Based on Dixon’s up-and-down method, the median effective concentration was calculated. RESULTS: The quadriceps strength was similar between the 2 groups, both at 30 min after adductor canal block and during recovery from general anesthesia in the Postanesthesia Care Unit. None of the patients in this study exhibited bradycardia or hypotension. The median effective concentration of ropivacaine for adductor canal block was 0.29% (95% confidence interval [CI], 0.28–0.31%) in group RD, which was lower than that in group R (0.38% [95% CI, 0.36–0.41%]). CONCLUSIONS: This study found perineural dexmedetomidine 1 μg/kg could reduce the median effective concentration of ropivacaine for the adductor canal block.